KESALAHAN HITUNG PENGURANGAN BILANGAN CACAH BAGI SISWA SD - Wahyudi Wahyudi (PAEDAGOGIA, 2009)
The objective of this research is to know the kinds of error patterns, reasons, and the problems of solving whole number subtraction. The research used qualitative approachwithCollaborativeActionResearchatgradeIIISDNegeri2Panjer,Kebumen. Theresultoftheresearchshowedthat(1)kindsoferrorpatternsare:readingandwriting thenumber;subtractionconceptfromtheones,thetens,thehundredsandthethousands; incomplete algorithm; random error; place value; basic fact; the big number is subtracted by the little number; error pattern 0 -a = a; error pattern a-b = 0 if a < b; and not remembering subtracting after borrowing, (2) The error patterns were done by students because they didn't understand symbol of number, subtraction concept, basic fact of subtraction, place value; and they didn't remember to subtract when they were regrouping, answering estimation; not being care, and writing the number, (3) To solve the problem of subtracting whole number at student grade III elementary school, the researcher conducted remedial teaching to find the students' error patterns and to fit the hierarchicalstudyofwholenumbersubtraction.